2000
DOI: 10.1212/wnl.54.12.2269
|View full text |Cite
|
Sign up to set email alerts
|

A 5-month, randomized, placebo-controlled trial of galantamine in AD

Abstract: Galantamine 16 and 24 mg/day significantly benefits the cognitive, functional, and behavioral symptoms of AD as compared with placebo. Slow dose escalation appears to enhance the tolerability of galantamine, minimizing the incidence and severity of adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
614
3
18

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 844 publications
(661 citation statements)
references
References 28 publications
26
614
3
18
Order By: Relevance
“…Clinical evidence 7,40,41 suggests that allowing a minimum interval of 4 weeks between dose increases significantly reduces the occurrence of acute gastrointestinal AEs with all ChE inhibitors. For example, slow dose escalation of donepezil resulted in a reduction in reported acute cholinergic AEs to close to placebo levels.…”
Section: Importance Of Slow Dose Escalationmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical evidence 7,40,41 suggests that allowing a minimum interval of 4 weeks between dose increases significantly reduces the occurrence of acute gastrointestinal AEs with all ChE inhibitors. For example, slow dose escalation of donepezil resulted in a reduction in reported acute cholinergic AEs to close to placebo levels.…”
Section: Importance Of Slow Dose Escalationmentioning
confidence: 99%
“…40 Similar findings have been noted for galantamine: the dropout rate due to AEs fell from 23% with 1-week titration steps 42 to 10% with 4-week steps. 7 With rivastigmine treatment it is particularly important to ensure a 4-week interval between dose increases due to the ability of this agent to potentially increase central ACh levels. 39 This dose-escalation schedule led to an AE dropout rate of just 2% with rivastigmine treatment 41 compared with 14% and 9% using 1-and 2-week gaps, respectively.…”
Section: Importance Of Slow Dose Escalationmentioning
confidence: 99%
See 1 more Smart Citation
“…In a 5-month placebo-controlled study in mild to moderate AD patients, galantamine was associated with improvement in behavior and functioning as measured by the Clinician's Interview-Based Impression of Change, Caregiver Input, and AD Cooperative Study ADL Inventory, as well as improvement in cognition as measured by the AD Assessment Scale cognitive subscale [29]. In another study in mild-moderate AD patients, improvements in functioning and cognition were observed at 6 months on galantamine versus placebo [30].…”
Section: Other Acetylcholinesterase Inhibitors In Alzheimer's Diseasementioning
confidence: 99%
“…Even in the absence of neuronal loss, the accumulation of such tangles in the NBM can be associated with a decrease in cholinergic neurotransmission as revealed by postmortem counts of cholinergic axons (Geula and Mesulam, 1989) and by in vivo SPECT mapping of cholinergic terminals (Kuhl et al, 1996). In animal studies (e.g., Weible et al, 2004;Woodruff-Pak et al, 2001) and in patients with Alzheimer's disease cognitive improvement can be achieved by nicotinergic as well as muscarinic receptor action (Oh et al, 2005;Raskind et al, 2000;Tariot et al, 2000).…”
Section: Introductionmentioning
confidence: 99%